Geochronology and petrogenesis of the lower Miocene felsic rocks: New evidence for initiation of post-collisional magmatism in the SW Malatya-Eastern Anatolia (Turkey) - Ertuerk, Mehmet Ali; Kara, Hatice; Sar, Abdullah; Yilmaz, Isak; Aysal, Namik (Slovak Acad Sciences Geological Inst, 2023)
The Southeast Anatolian Orogenic Belt (SAOB) consists of various tectono-magmatic and tectono-stratigraphic units such as metamorphic massifs, granitoids, ophiolites and volcanic rocks. In this study, we report new zircon U-Pb LA-ICP-MS ages, Sr-Nd isotope analysis and whole-rock geochemistry from Miocene felsic (dacitic and rhyolitic) rocks cross-cutting the Permo-Triassic Malatya metamorphic complex to determine the source of magmatism and magmatic processes in the region. The zircon U-Pb crystallisation ages are between 16.66 & PLUSMN; 0.23 Ma and 16.83 & PLUSMN; 0.094 Ma, implying the start of the post-collisional volcanism in the Early Miocene (Burdigalian) period. Volcanic rocks have calc-alkaline and high-K calc-alkaline characters. The 87Sr/86Sr values for the felsic volcanics range between 0.707098 and 0.711703. The initial 143Nd/144Nd ratios are between 0.512446 and 0.512469, and the & epsilon;Nd values vary from -3.12 to -3.66. The Nd (TDM) model ages are between 1.05 and 1.13 Ga. Negative & epsilon;Nd values and Nd (TDM) model ages show great similarities with the Precambrian basement in Turkey, Iran and the Arabian peninsula. Energy-constrained assimilation- fractional crystallisation (EC-AFC) models testing different crustal sources using Sr-Nd isotope data show that primary magmas contain significant crustal melt contributions. Geochemical data indicate that the felsic rocks may have originated from crust-derived melts mixed with lithospheric mantle-derived mafic melts during its residence in the upper crust in a post-collisional tectonic setting.
Keywords: felsic rocks; zircon U-Pb ages; lithospheric mantle; upper crust; post-collisional volcanism; Eastern Turkey